Fruit Set Percentage And Oil Palm Production In Smallholder Plantations In Sungai Kunyit Village, Sekadau Hilir Sub-District,Sekadau District. - Ferdyanto, Pius Paternus; Supriyanto, Supriyanto; Sulistyowati, Henny (Perkebunan dan Lahan Tropika, 2025)
The productivity of oil palm between smallholder farmers and companies influenced by cultivation practices, such as fertilization, pruning, pest and disease control, and the pollination process. This study aims to analyze the fruit set percentage and oil palm production in Dusun Amak, Sungai Kunyit Village, Sekadau Hilir Sub-district, and to identify the influence of pollinating insect populations and the percentage of male flowers on fruit set. The research was conducted in smallholder oil palm plantations using survey and interview methods. The survey included tree census, fruit and bunch sampling, pest and disease observation, pollinating insect counting, and average bunch weight measurement. Unstructured interviews were conducted with farmers to supplement the data. The results showed a fruit set percentage of 67.87%, lower than the optimal potential of 80% for 10-year-old oil palm trees. Although male flowers were sufficient, the low population of pollinating insects (Elaeidobius kamerunicus) led to suboptimal pollination, resulting in a lower fruit set.